Incidence and Clinical Characteristics of Childhood Glaucoma: A Population-Based Study - Aponte, Elisabeth P. (2010)
OBJECTIVE: To describe the incidence and clinical characteristics of childhood glaucoma in a defined population of the United States. METHODS: The medical records of all patients (< 20 years) meeting diagnostic criteria for glaucoma or glaucoma suspect, as residents of Olmsted County, Minnesota, from January 1, 1965, through December 31, 2004 were reviewed. RESULTS: Thirty children were diagnosed with glaucoma during the 40-year study period. The age- and sex-adjusted incidence of childhood glaucoma was 2.29 (95% CI: 1.47–3.12) per 100,000 residents < 20 years of age, with the following types and incidences: 19 acquired (1.46/100,000; 95% CI: 0.80–2.12), 6 secondary (0.45/100,000; 95% CI: 0.08–0.82) and 5 with primary glaucoma (0.38/100,000; 95% CI: 0.05–0.72). The birth prevalence of primary congenital glaucoma during the 40-year period was 1 in 68,254 births or 1.46 per 100,000 births (95% CI: 0.03–8.16). Twenty-four glaucoma suspects were also identified, yielding an incidence of 1.9 per 100,000 patients < 20 years of age (95% CI: 1.14–2.66). CONCLUSION: The incidence of childhood glaucoma in this population was 2.29 per 100,000 or 1 in 43,575 for patients <20 years of age. Acquired and secondary forms of glaucoma were the most common while congenital and juvenile glaucoma were rare.